Paper Biosecurity and Smallholder Vulnerability to Contagious Livestock Diseases in Indonesia - Nayla Alya Syamsiputri (Punggawa Global Research: Jurnal Multidisiplin, 2026)
Contagious livestock diseases reveal a persistent weakness in smallholder biosecurity. Formal guidance may define reporting, movement control, vaccination, and farm-level prevention, yet those measures often lose force once they reach household farms with limited space, uneven veterinary access, and strong dependence on livestock as economic assets. Drawing on secondary data from livestock statistics, disease reports, policy documents, and scientific literature published between 2019 and 2026, this study examines why formal biosecurity has not been sufficient to protect smallholder livestock systems from foot-and-mouth disease and lumpy skin disease in Indonesia. The analysis combines policy document review, descriptive epidemiological reading, and gap analysis. The findings indicate that biosecurity is administratively present but operationally thin. Formal documents allocate responsibility to farmers and veterinary authorities with reasonable clarity, while the practical conditions needed for early reporting, isolation, vaccination continuity, and movement control remain uneven. Foot-and-mouth disease exposes the fragility of rapid reporting and animal movement control under high transmission pressure, whereas lumpy skin disease highlights the need for sustained field response and cattle-value protection after public urgency declines. The article develops the concept of paper biosecurity to describe this mismatch and proposes minimum viable biosecurity as a more feasible direction for smallholder settings. Biosecurity policy becomes stronger when technical standards are translated into affordable routines, trusted reporting channels, and locally supported veterinary action.